Antonio Azuela de la Cueva. La ciudad, la propiedad privada y el derecho. México : El Colegio de México, 1989. 278 p. - Muñoz Contreras, María Elena (El Colegio de México A.C., 1990)
ANTONIO AZUELA DE LA CUEVA, La ciudad la propiedad privada y el derecho, El Colegio de México, 1989.